Internet of Things (IoT) sebagai Solusi Ketahanan Pangan di Tengah Bencana Sosial - Maulidia, Syaqilla; Camila, Naina (Program Studi Teknik Informatika Universitas Paramadina, 2025)
Food security in Indonesia faces various challenges, including climate change, population growth, and potential social disasters such as conflict or unequal food distribution. The utilization of the Internet of Things (IoT) is an alternative solution to support national food security. This paper aims to examine the role of IoT in improving agricultural efficiency to prevent crises and social disasters due to food scarcity. The method used is a literature study from various relevant sources. The results show that IoT can assist in land monitoring, automatic irrigation, weather prediction, and pest and disease detection. This technology increases productivity and makes food distribution more equitable. In conclusion, the implementation of IoT in the agricultural sector has the potential to prevent the impact of social disasters by strengthening food security through a smarter system.